A Rapid Method to Estimate Hepatocyte Loss Due to Drug‐Induced Liver Injury. Issue 3 (2nd November 2018) - Chung, Jae‐Yong; Longo, Diane M.; Watkins, Paul B.
Abstract : It is not currently possible to rapidly estimate the extent of hepatocyte loss during drug‐induced liver injury (DILI). We used a proprietary mechanistic model (DILIsym) to estimate percentage hepatocyte loss due to DILI that resulted from four different patterns of serum alanine aminotransferase (ALT) over time: rapid onset and rapid decrease in ALT levels, moderate onset and moderate decrease in ALT levels, moderate onset and extended duration (over 1 month) of ALT elevations, and an ALT profile with multiple peaks. Using these data, we derived a novel parameter, PALT = ALT_AUC*Peak ALT 0.18 /10 5 ((IU/L) 2 *h), where AUC is area under the curve, that correlated well with hepatocyte loss estimates derived by DILIsym in patients with DILI due to six different hepatotoxic drugs. Although further validation will be required, the fact that PALT can be derived rapidly using publicly available pharmacokinetic software may make it a useful parameter to improve the safety of drugs.